2004
DOI: 10.1111/j.1527-3466.2004.tb00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Potential of Lomerizine, a Ca2+ Channel Blocker as an Anti‐Glaucoma Drug: Effects on Ocular Circulation and Retinal Neuronal Damage

Abstract: Glaucoma is defined as an optic neuropathy with characteristic changes in the optic nerve head and ultimate loss of visual field. Previous studies have suggested that (a) mechanical damage due to raised intraocular pressure and (b) a compromised tissue circulation in the optic nerve head play significant roles in the development of glaucomatous damage in the optic nerve head. Recently, we found that lomerizine, a new Ca(2+) channel blocker, increased ocular circulation and protected neuronal cells against reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 69 publications
0
16
0
1
Order By: Relevance
“…Of the four selected compounds, manidipine, lacidipine, and benidipine target L-type calcium channels and are clinically used as antihypertensive agents [34], whereas lomerizine targets both Land T-type calcium channels and is generally used in the clinical treatment of migraines [35], as well as the experimental treatment of glaucoma and optic nerve injury [36].…”
Section: Ccbs Inhibit Sphere Formation and Induce Cell Death In Ovarimentioning
confidence: 99%
“…Of the four selected compounds, manidipine, lacidipine, and benidipine target L-type calcium channels and are clinically used as antihypertensive agents [34], whereas lomerizine targets both Land T-type calcium channels and is generally used in the clinical treatment of migraines [35], as well as the experimental treatment of glaucoma and optic nerve injury [36].…”
Section: Ccbs Inhibit Sphere Formation and Induce Cell Death In Ovarimentioning
confidence: 99%
“…Specific antihypertensive agents could have different effects on POAG. In vitro and in vivo studies with rabbits suggested that calcium channel antagonists may increase ocular circulation and protect neuronal cells against retinal neurotoxicity (Hara et al 2004). In patients with ocular vasospasm and normal tension glaucoma, the use of calcium channel antagonist agents was suggested to reduce vasospasm in some publications (Gaspar et al 1994;Schmidt et al 1996).…”
Section: Effects Of Systemic Medicationsmentioning
confidence: 99%
“…To assess the protective effects of lomerizine against neuronal loss in dorsal LGN (dLGN) and SC, sections stained with cresyl violet were used for neuronal cell counting: six sections for dLGN (L1: bregma −1.70 mm, L2: −1.92 mm, L3: −2.14 mm, L4: −2.36 mm, L5: −2.58 mm, and L6: −2.80 mm) and four for SC (S1: bregma −3.30 mm, S2: −3.52 mm, S3: −3.74 mm, and S4: −3.96 mm) in each mouse ( Figure 1). The area of each field used for this cell counting was 0.036 mm 2 ( Figure 1C & E). Cell counts were carried out under a microscope at 400× magnification in a masked fashion by a single observer (Y.…”
Section: Neuron Numbers In Dlgn and Scmentioning
confidence: 99%